OMNIBUSLAW IS LINKED TO THE ACHIEVEMENT OF COUNTRY GOALS - Andi Batubara; Amiludin Amiludin; Muhammad Asmawi (Jurnal Hukum Replik, 2021)
Omnibuslaw, are a legal product to simplify legislation which is previously, reputed overlapping, with make efficiency process/change information regulations, to delete ego sectoral. However in the formation process, and legalization break Government Regulation Number 12 of the Year 2011, concerning Formating Government Regulations, and be in conflict of interest business politic from oligarchy network available at Parlement, where 55 % (fifty-five percent) member of Parliament is a businessman so that the product of law salted fulfilled with interest authority party and the winner of selection. And if studied further, it will be found articles that are not in favor of the workforce, such as the article on outsourcing, there is no limit on the types of work that may use outsourcing, then all types of work in the main job or main work in a company can use outsourced employees. Thus, the workforce no longer has clarity on wages, health insurance, pension insurance, and job security. The Specific Time Work Agreement system is not explicitly regulated regarding the period, it is only stated that it will be regulated in a Government Regulation or technical rules derived from the Law, Long Leave is submitted to work agreements, company regulations, or work agreements together so that the legal certainty needs to be questioned. Concerning wages for severance pay in the Omnibus Law, workers who are affected by the termination of employment or stop working for other reasons may now no longer receive severance pay.Keywords: Power; Political Instristing; Political Law, Law Product.